Effectiveness of the Implementation of Restitution Payment Decisions for Victims of Criminal Acts of Fraud - Kusuma, Agung Jaya (Jurnal Hukum Khaira Ummah, 2025)
This study aims to determine and analyze the effectiveness and obstacles in the implementation of restitution payment decisions for victims of fraud in decision Number 343/Pid.Sus/2022/PN.Bjm. This study uses a sociological legal approach method, analytical descriptive research specifications, the data used are primary data and secondary data. Data collection methods include field studies and literature studies, while the data analysis method is qualitative. The theories used in this study are the theory of legal effectiveness and the theory of legal certainty. Based on the results of the study, it can be concluded that the implementation of restitution payment decisions for victims of fraud at the Banjarmasin District Attorney's Office in decision Number 343/Pid.Sus/2022/PN.Bjm has not been effective. This is because it is constrained by the limitations of the law in regulating the technical implementation of restitution payments by the prosecutor's office, the convict's assets are insufficient to pay restitution, and difficulties in tracing assets. The solution to overcome these obstacles is that it is necessary to immediately create regulations related to technical guidelines for the prosecutor's office in managing the assets of convicts as restitution payments, the prosecutor's office coordinates with LPSK, KPKNL to hold FGD meetings with victims to reach an agreement, cooperation with the Financial Services Authority (OJK) or other related institutions to accelerate the asset identification process.